Patient Satisfaction with the National Health Insurance Scheme Dental Service in Kupang, East Nusa Tenggara - Manginar Sidabutar; Friska D Simamora; Faber Sidabutar (Journal of Indonesian Dental Association, 2019)
Introduction: Patients with government insurance such as National Health Insurance Scheme (BPJS) use capitation system with low dental services payment. Patients should be treated professionally without considering payment system whether government or private insurance. Objective: The aim of this study is to know the satisfaction of the patients who visited dental treatment in BPJS facilities. Method: Data collected using structured questionnaire from Bhayangkara, W.Z Yohanes General Hospital, Public Health center in Kupang Kota and Pasir Panjang from June 1st – October 31st 2018. There were 46 samples from each hospital and 45 from each public health center. The study variables were patient satisfaction with dental health service accessibility, communication between patient, dentist, and staff, and safety and technology during the dental treatment. Result: Patients aged between 20 and 45 years old were the most common users of dental health services (59%). Patients with BPJS and Kartu Indonesia Sehat (KIS) insurance who paid by government were the most common patients to visit a dental health service facility (83.1%). Easy access to see the dentist was highly satisfying for 83.1% of the respondents. The BPJS patients were satisfied with the results of dental treatment (68.3%) and, concerning communication, 71.6% of the patients were satisfied with the dentist’s friendliness. Patients were quite satisfied with the ease of contacting the dentist (89.1%). Regarding instrument sterilization, 26.2% of the respondents were quite satisfied. On communication related to the dental treatment procedure, 23.5% of the respondents were quite satisfied. Regarding the technology in dental treatment, 30.6% of the respondents were quite satisfied. Conclusion: BPJS patients were satisfied with dental health services which most of them had a low educational background, were female, worked as a private employee or homemaker and were patients with governmental aid.